Matrix vesicles from chondrocytes and osteoblasts: Their biogenesis, properties, functions and biomimetic models - Bottini, Massimo; Mebarek, Saida; Anderson, Karen L.; Strzelecka-Kiliszek, Agnieszka; Bozycki, Lukasz; Simão, Ana Maria Sper; Bolean, Maytê; Ciancaglini, Pietro; Pikula, Joanna Bandorowicz; Pikula, Slawomir; Magne, David; Volkmann, Niels; et al. (Biochimica et biophysica acta, 2018)
Matrix vesicles (MVs) are released from hypertrophic chondrocytes and from mature osteoblasts, the cells responsible for endochondral and membranous ossification. Under pathological conditions, they can also be released from cells of non-skeletal tissues such as vascular smooth muscle cells. MVs are extracellular vesicles of approximately 100–300nm diameter harboring the biochemical machinery needed to induce mineralization. The review comprehensively delineates our current knowledge of MV biology and highlights open questions aiming to stimulate further research. The review is constructed as a series of questions addressing issues of MVs ranging from their biogenesis and functions, to biomimetic models. It critically evaluates experimental data including their isolation and characterization methods, like lipidomics, proteomics, transmission electron microscopy, atomic force microscopy and proteoliposome models mimicking MVs. MVs have a relatively well-defined function as initiators of mineralization. They bind to collagen and their composition reflects the composition of lipid rafts. We call attention to the as yet unclear mechanisms leading to the biogenesis of MVs, and how minerals form and when they are formed. We discuss the prospects of employing upcoming experimental models to deepen our understanding of MV-mediated mineralization and mineralization disorders such as the use of reconstituted lipid vesicles, proteoliposomes and, native sample preparations and high-resolution technologies. MVs have been extensively investigated owing to their roles in skeletal and ectopic mineralization. MVs serve as a model system for lipid raft structures, and for the mechanisms of genesis and release of extracellular vesicles. Matrix vesicles are extracellular vesicles that bind to collagen and can induce formation of apatitic mineral during physiological and ectopic mineralization. Lipid and protein compositions in matrix vesicles resemble those of lipid rafts. Mechanisms of the biogenesis of matrix vesicles and processes leading to mineral/apatite formation are still unclear. Proteoliposomes can serve as biomimetic models to understand matrix vesicle-mediated mineralization. [Display omitted] •This review addresses a series of questions about matrix vesicles and biomimetic models for matrix vesicles.•Matrix vesicles are roughly spherical extracellular vesicles of 100–300nm in diameter.•Preparation of hydrated samples is necessary for preserving matrix vesicles in their native state.•Mechanisms of the biogenesis of matrix vesicles are still unclear.•Proteoliposomes can serve as a model to understand matrix vesicle-induced mineralization.